2019
DOI: 10.1080/21681805.2019.1634147
|View full text |Cite
|
Sign up to set email alerts
|

Risk of urothelial cancer death among people using antihypertensive drugs—a cohort study from Finland

Abstract: Introduction:To analyse the association between antihypertensive (anti-HT) drug use and risk of urothelial cancer (UC) death. UC occur as bladder cancer (BCa) and upper tract urothelial carcinomas (UTUCs). Hypertension is a suggested risk factor for BCa and may impair disease prognosis. However it`s unclear if use of anti-HT drugs could improve prognosis of UC. Materials and Methods:We evaluated the association between use of anti-HT drugs and UC survival among 14,065 participants diagnosed with BCa and 1080 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 12 publications
4
12
0
Order By: Relevance
“…While beta blockers represented the most common antihypertensives in our analysis, no impact on RFS, CSS or OS was found. This is in line with findings by Dal Moro et al (20 patients) and Santala et al (500 patients) [ 8 , 9 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…While beta blockers represented the most common antihypertensives in our analysis, no impact on RFS, CSS or OS was found. This is in line with findings by Dal Moro et al (20 patients) and Santala et al (500 patients) [ 8 , 9 ].…”
Section: Discussionsupporting
confidence: 93%
“…A study evaluating the risk for urinary tract cancer development enrolling over 30,000 patients found no effect for ACEI, while ARB increased the risk [ 10 ]. Recently, a Finnish retrospective study evaluating the impact of antihypertensives on survival after bladder cancer diagnosis found no effect for ACEI, but an improved survival for ARB [ 9 ]. Of note, the positive ARB effect was only significant in the multivariate analysis for men, but not women.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a large nationwide Finnish cohort, the authors found a significant reduction in mortality due to breast cancer in RASB users, also featuring a dose-effect, suggesting a mechanistic association [ 84 ]. Similarly, concurring elements supported that urological cancer survival improved with RASB use [ 85 , 86 , 87 , 88 , 89 ]. In non-small-cell lung cancer, RASB use with platinum and taxol chemotherapy was associated with improved survival [ 90 , 91 ].…”
Section: Part 1: Renin–angiotensin System Blockers and Malignanciesmentioning
confidence: 84%